2017
DOI: 10.1088/0256-307x/34/1/017801
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence Kinetic Parameters of TLD-600 and TLD-700 after 252 Cf Neutron+Gamma and 90 Sr- 90 Y Beta Radiations

Abstract: The thermoluminescent (TL) properties such as glow curve structure, relative thermoluminescence sensitivity, dose response linearity of lithium fluoride thermoluminescent dosimeters 6LiF:Ti,Mg (TLD-600) and 7LiF:Ti,Mg (TLD-700) are investigated after irradiation 252Cf neutron+gamma and 90Sr-90Y beta sources at room temperature and then the obtained results are compared. The kinetic parameters, namely the order of kinetics b, activation energy and the frequency factor s, are calculated using the computerized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
4
2
1
Order By: Relevance
“…However, thermal quenching was not observed in both TLD-600 and TLD-700 at 1000mGy and using ROI. When the results obtained for TLD-600 and TLD-700 in our study are compared directly with the study of İflazoğlu et al [18], thermal quenching was reported in İflazoğlu et al [18], but no thermal quenching in our study in the order of Gy. As a conclusion, the findings obtained in the above mentioned studies [15,[17][18] in the order of Gy do not seem compatible with those obtained in our study.…”
Section: Thermal Quenching Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…However, thermal quenching was not observed in both TLD-600 and TLD-700 at 1000mGy and using ROI. When the results obtained for TLD-600 and TLD-700 in our study are compared directly with the study of İflazoğlu et al [18], thermal quenching was reported in İflazoğlu et al [18], but no thermal quenching in our study in the order of Gy. As a conclusion, the findings obtained in the above mentioned studies [15,[17][18] in the order of Gy do not seem compatible with those obtained in our study.…”
Section: Thermal Quenching Resultssupporting
confidence: 74%
“…When the results obtained for TLD-600 and TLD-700 in our study are compared directly with the study of İflazoğlu et al [18], thermal quenching was reported in İflazoğlu et al [18], but no thermal quenching in our study in the order of Gy. As a conclusion, the findings obtained in the above mentioned studies [15,[17][18] in the order of Gy do not seem compatible with those obtained in our study. The Tmax values for the main dosimetric peak for both TLD-600 and TLD-700 were reported at ~245°C for the heating rate of 1°C/s in these studies of [15,[17][18].…”
Section: Thermal Quenching Resultssupporting
confidence: 74%
See 3 more Smart Citations